Tuberculosis Situation in Bogra District: After One Decade National TB Control Programme (TAJ: Journal of Teachers Association, 2009)
The ongoing national TB control programme (NTP) of Bangladesh had started from 1993 and had expanded at all upazilas in collaboration with partner NGOs by June 1998. The NTP is following DOTS strategy with target 70% case detection and 85% cure rate. By this time more than a decade has passed but total achievement of NTP is yet remain mask due to absence of exact statistic on tuberculosis situation in our country. doi: 10.3329/taj.v18i2.3175 TAJ 2005; 18(2): 98-105